Evaluation of a novel recombinant strain of infectious bronchitis virus emerged from three attenuated live vaccine strains. (March 2022) - Gong, Huiling; Ni, Ruiqi; Qiu, Rongbin; Wang, Fuyan; Yan, Wenjun; Wang, Kailu; Li, Hao; Fu, Xue; Chen, Liang; Lei, Changwei; Wang, Hong-ning; Yang, Xin
Abstract: Infectious bronchitis virus (IBV) causes avian infectious bronchitis (IB) and there are multiple serotypes worldwide originating from deletions, insertions, point mutations, and RNA recombination. In this study, a recombinant IBV, named CK/CH/MY/2020, was isolated from southwest China. Sequencing and phylogenetic analysis revealed that CK/CH/MY/2020 consists of 27, 614 nucleotides and belongs to the GI-28 genotype. Moreover, the strain is a recombination product originating from three live attenuated vaccine strains (H120, 4/91, and LDT3-A). The recombination is complicated involving at least nine recombination sites; the first 3/5 portion is mainly composed of H120 and 4/91, and the second 2/5 contains LDT3-A. Pathogenicity analysis showed that CK/CH/MY/2020 could cause respiratory and kidney diseases in chickens resulting in moderate mortality. Therefore, the recombinant strain is more virulent than the attenuated vaccine strains. This study shows that even in the absence of wild strains, the recombination and revirulence of multiple attenuated vaccines could occur simultaneously, which also highlights the continuous evolution in IBV. Highlights: A new recombinant IBV strain was identified in southwest China. CK/CH/MY/2020 strain consists of three live attenuated vaccines: H120, 4/91, and LDT3-A. The recombinant strain CK/CH/MY/2020 is virulent and caused clinical reaction and death in chickens.